2022
DOI: 10.1155/2022/6380719
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] University Network and New Media Advertising Teaching Design Features and Influence: Environmental Perspective Analysis in Campus Humanistic Governance

Abstract: Under the background of network development in the new era, the integration of multimedia technology and information technology promotes the development of teaching environment. Based on the influence of humanistic governance environment, the university network environment and the advertising teaching environment are constantly integrating new elements with the development of the times, becoming the key point to guarantee the teaching quality. In the research, the relevant data and information were collected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%